IMPACT OF DIGITAL PAYMENT SYSTEMS ON CONSUMER BEHAVIOR AND BUSINESS GROWTH: AN EMPIRICAL STUDY WITH REFERENCE TO TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of digital payment systems on consumer behavior and business growth in Tirunelveli district. Using a cross-sectional survey of consumers (n = 120) and merchant-feedback, the research examines adoption rates, frequency of use, and the perceived benefits and constraints of digital payments. Quantitative analyses include simple percentage distributions, a chi-square test to examine association between education level and adoption, and Garrett’s ranking technique to prioritize factors influencing adoption. Results indicate a significant association between education and digital payment adoption, with security and convenience ranking highest as drivers for adoption. Recommendations focus on digital literacy programs, merchant incentives, and enhanced security communication to strengthen adoption and support business growth.